Is the ‘docta ignorantia’ a form of ‘philosophari in Maria’? - Szalay, Mátyás (Warszawskie Studia Teologiczne, 2020)
Cusanus’ learned ignorance is a complex notion that is explained as a form of introduction into Christian wisdom. The different meanings of how God exceeds our conceptual reach and remains ineffable despite all metaphorical approaches are laid out in three steps: the first is devoted to God (conicidencia oppositorum), the second to the Universe (complicatio/explicatio) and the third to the God-man, Jesus Christ. Jesus Christ is represented here as an intermediary, as measure and mediator between God and creation, the finite and the infinite. Along these lines I highlight three main aspects of docta ignoratia as especially relevant for contemporary thinking. These aspects will be used to evaluate the extent to which Cusanus’ powerful proposal to reinterpret Christian reality can help us respond to Pope John Paul II’s exhortation in Fides et ratio to understand and to exercise Christian reflection as philosophari in Maria.